2023
DOI: 10.1021/acs.inorgchem.3c00320
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Reactivity Studies of Mononuclear Tetrahedral Copper(II)–Halide Complexes

Abstract: Structures, physicochemical properties, and reactivity of the whole series of copper(II)−halide complexes (1 X ; X = F, Cl, Br, and I) were examined using a TMG 3 tach tridentate supporting ligand consisting of cis,cis-1,3,5-triaminocyclohexane (tach) and N,N,N′,N′-tetramethylguanidine (TMG). The tach ligand framework with the bulky and strongly electron-donating TMG substituents enforces the copper(II) complexes to take a tetrahedral geometry, as inferred from the electron paramagnetic resonance (EPR) spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…To explore the redox reactivity of such tetrahedral copper( ii ) complexes, we have developed a series of copper( ii ) complexes, [Cu II (TMG 3 tach)X] + ( 1 X ), where TMG 3 tach is an N 3 -tridentate ligand consisting of cis,cis -1,3,5-triaminocyclohexane (tach) and N , N , N ′, N ′-tetramethylguanidino (TMG) substituents, and X is an anionic co-ligand (F − , Cl − , Br − , I − , MeO − , C 6 F 5 O − , C 6 F 5 S − , or ROO − ). 1–3 Reactivity studies of the halide complexes demonstrated that they undergo Cu II –X bond cleavage, and in the case of X = F − , Cl − , and Br − , they induce C–H bond activation of an external substrate, such as 1,4-cyclohexadiene (CHD) with a weak C–H bond (76.0 ± 1.2 kcal mol −1 ), 4 to give the corresponding copper( i ) complex and benzene as the oxidation product. 3 Such C–H bond activation reactivity of transition-metal halide complexes has been reported by using high-valent transition-metal halide complexes of Ni III , Pd IV , Cu III , and Au III , where the higher oxidation state of the metal ions induces homolytic cleavage of the metal–halide bond.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the redox reactivity of such tetrahedral copper( ii ) complexes, we have developed a series of copper( ii ) complexes, [Cu II (TMG 3 tach)X] + ( 1 X ), where TMG 3 tach is an N 3 -tridentate ligand consisting of cis,cis -1,3,5-triaminocyclohexane (tach) and N , N , N ′, N ′-tetramethylguanidino (TMG) substituents, and X is an anionic co-ligand (F − , Cl − , Br − , I − , MeO − , C 6 F 5 O − , C 6 F 5 S − , or ROO − ). 1–3 Reactivity studies of the halide complexes demonstrated that they undergo Cu II –X bond cleavage, and in the case of X = F − , Cl − , and Br − , they induce C–H bond activation of an external substrate, such as 1,4-cyclohexadiene (CHD) with a weak C–H bond (76.0 ± 1.2 kcal mol −1 ), 4 to give the corresponding copper( i ) complex and benzene as the oxidation product. 3 Such C–H bond activation reactivity of transition-metal halide complexes has been reported by using high-valent transition-metal halide complexes of Ni III , Pd IV , Cu III , and Au III , where the higher oxidation state of the metal ions induces homolytic cleavage of the metal–halide bond.…”
mentioning
confidence: 99%
“…1–3 Reactivity studies of the halide complexes demonstrated that they undergo Cu II –X bond cleavage, and in the case of X = F − , Cl − , and Br − , they induce C–H bond activation of an external substrate, such as 1,4-cyclohexadiene (CHD) with a weak C–H bond (76.0 ± 1.2 kcal mol −1 ), 4 to give the corresponding copper( i ) complex and benzene as the oxidation product. 3 Such C–H bond activation reactivity of transition-metal halide complexes has been reported by using high-valent transition-metal halide complexes of Ni III , Pd IV , Cu III , and Au III , where the higher oxidation state of the metal ions induces homolytic cleavage of the metal–halide bond. 5–14 In the case of 1 X , on the other hand, the metal centre has a normal Cu II oxidation state, but not a high-valent metal ion such as Cu III .…”
mentioning
confidence: 99%
See 1 more Smart Citation